PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS IV SDN 010 TEMBILAHAN HULU - Ariana (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This study aimed to determine the effect of the problem-based learning model on improving students' critical thinking skills. Critical thinking refers to a person's ability to find information and solve a problem. The problem-based learning model is believed to stimulate students' ability to think creatively, analytically, systematically, and logically to find alternative problem solving through empirical data exploration to foster scientific attitudes. This study used Classroom Action Research (CAR) using the Kemmis and Mc. Taggart model. This study was conducted at SDN 010 Tembilahan Hulu. The subjects of this study were 28 students at grade IV. This study found that the classical completeness of students' critical thinking skills in Cycle I was 40%, and the average score was 53.4. Then, in Cycle II, the classical completeness was 80%, and the average score was 77. Therefore, the problem-based learning model improved students' critical thinking skills and attractiveness towards mathematics